Linear and nonlinear hearing aid fittings -- 1. Patterns of benefit. - Gatehouse S; Naylor G; Elberling C (International Journal of Audiology, 2006)
We evaluated the benefits of fast-acting WDRC, slow-acting AVC, and linear reference fittings for speech intelligibility and reported disability, in a within-subject within-device masked crossover design on 50 listeners with SNHL. Five hearing aid fittings were implemented having two compression channels and seven frequency bands. Each listener sequentially experienced each fitting for a 10-week period. Outcome measures included speech intelligibility under diverse conditions and self-reported disability. At a group level, each nonlinear fitting was superior to the linear references for benefits in listening comfort, listener satisfaction, reported intelligibility and speech intelligibility. Slow-acting AVC outperformed the fast-acting WDRC fittings for listening comfort, while for reported and measured speech intelligibility the converse was true. For listener satisfaction there were no group differences between the nonlinear fittings. Analysis in terms of fittings for individual listeners revealed subsets with definite divergences from the group data and hence a need for candidature criteria. There are systematic differences between the benefits of nonlinear and linear fittings, and also within nonlinear fittings with fast versus slow time constants. The patterns of benefit and individual optima depend on the domain of outcome being assessed.